Development of Student Worksheets (LKPD) Based on the Conceptual Change Model (CCM) to Minimize Misconceptions in Human Circulatory System Material for Elementary School Students - Azizah, Dera Mutia; Desstya, Anatri (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Science education in elementary schools requires the cultivation of accurate conceptual understanding to minimize misconceptions. However, misconceptions are still found in the material on the circulatory system. This study aims to: a) describe the existing science worksheets in the field, b) test the validity of CCM-based worksheets, and c) test the practicality of CCM-based worksheets.Methodology: This research is a Research and Development (R&D) study using the 4-D model (Define, Design, Development, Disseminate), but limited to the development stage. The subjects included 24 students and educators of class VI.3 at SD Muhammadiyah 16 Surakarta. Data collection techniques included observation, interviews, documentation, and Three-tier multiple choice diagnostic tests. The LKPD was validated by subject matter experts, media experts, and practitioners. Data were analyzed qualitatively and quantitatively.Results: The results showed that: a) the LKPD on the circulatory system was ready for use, b) the CCM-based LKPD obtained 85% validation from subject matter experts and 87.5% from media experts (both Very Valid), c) the practicality test by practitioners was 85% (Very Practical). These results confirm that CCM-based LKPD is feasible and practical for minimizing misconceptions in circulatory system material.Applications/Originality/Value: The validation and practicality results show that CCM-based LKPD is ready to be tested in IPAS learning on a wider scale. Although it has been declared Valid and Practical, it is necessary to establish a hypothesis that requires empirical testing in the future with a control group and pre/post-test design to test the effectiveness of this LKPD.